2011
DOI: 10.1017/s1355617711000348
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Emotion and Conflict Processing in HIV Infection with and without Alcoholism Comorbidity

Abstract: Alcoholism and HIV-1 infection each affect components of selective attention and cognitive control that may contribute to deficits in emotion processing based on closely interacting fronto-parietal attention and frontal-subcortical emotion systems. Here, we investigated whether patients with alcoholism, HIV-1 infection, or both diseases have greater difficulty than healthy controls in resolving conflict from emotional words with different valences. Accordingly, patients with alcoholism (ALC, n = 20), HIV-1 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…Our task, which requires subjects to match the color of a cue to that of a word, recently showed that patients with alcoholism have greater difficulty than controls (CTL) in resolving conflict arising from emotional words (Schulte et al, 2011) similar to the observed attentional bias to alcohol words (Field et al, 2012;Johnsen et al, 1994). The overarching hypothesis of the current study is that chronic alcohol consumption compromises neural regulation of prefrontal monitoring and midbrain reward mechanisms within the mesocorticolimbic system.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our task, which requires subjects to match the color of a cue to that of a word, recently showed that patients with alcoholism have greater difficulty than controls (CTL) in resolving conflict arising from emotional words (Schulte et al, 2011) similar to the observed attentional bias to alcohol words (Field et al, 2012;Johnsen et al, 1994). The overarching hypothesis of the current study is that chronic alcohol consumption compromises neural regulation of prefrontal monitoring and midbrain reward mechanisms within the mesocorticolimbic system.…”
Section: Introductionmentioning
confidence: 51%
“…The Stroop effect is defined as the difference in reaction time (RT) to incongruent and congruent stimuli. For incongruent-nonmatch color-Stroop conditions, the cue color always matched the word content (eg, red cue, word RED written in green font color) (Schulte et al, 2005(Schulte et al, , 2008(Schulte et al, , 2011(Schulte et al, , 2012.…”
Section: Stimuli and Experimental Designmentioning
confidence: 99%
“…The first is emotion discrimination and identification, which differentiated the drinking group from the no/low drinkers. Impairment in emotion detection and expression of greater negative emotional states has been documented using several different paradigms in adult alcoholics in recovery (Charlet et al, 2014; Clark, Oscar-Berman, Shagrin, & Pencina, 2007; Kornreich et al, 2013; Maurage, Campanella, Philippot, Martin, & de Timary, 2008; O’Daly et al, 2012; Schulte, Müller-Oehring, Rohlfing, Sullivan, & Pfefferbaum, 2011). Misperception of emotion has been speculated to contribute to misinterpretation of intent of another person, potentially serving as a source, for example, of argument or unwanted advances.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify Stroop effects within a block design, incongruent and congruent trials were never mixed within a block. Consistent with our experience with previous task versions of the Stroop Match-to-Sample task (Müller-Oehring et al 2013; Müller-Oehring et al 2015a, b; Schulte et al 2005; Schulte et al 2011; Schulte et al 2012), subjects were not aware about the blocked trial design, as indicated in post-scan interviews.…”
Section: Methodsmentioning
confidence: 70%